Underpricing in Indonesia non financial companies - Fadillah, Nisak Nur; Isbanah, Yuyun (Technium Social Sciences Journal, 2021)
The purpose of this research is to determine the effect of financial variables (ROE, DER, firm size) and non-financial variables (underwriter reputation, offer size, firm age) to underpricing rate. This research was conducted on non-financial companies that conduct IPO in Indonesia Stock Exchange in the period 2010-2016. Data collection techniques used are literature study and observation. Sampling is collected by using purposive sampling method that obtained 91 companies as research sample from population 156 companies. The model used to test the relationship between independent variables with dependent variable is multiple regression model. The results of multiple regression analysis showed that firm size variables affect the underpricing rate. While other independent variable have no effect on underpricing rate.